Legal doctrines in tax disputes: influence on law-making processes - Zaverukha, Oleh (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to topical problems in the tax and legal sphere regarding the impact of legal doctrines on law-making processes. The author paid the main attention in this research to a detailed analysis of theoretical and methodological aspects of the application of legal doctrine in tax disputes as a source of law, which made it possible to ascertain the relevance of the definition of the concept of legal doctrine and the implementation of a general systematic study of its features in the processes of law-making in Ukraine. At the same time, it was emphasized that doctrines exert an important influence not only on the law enforcer and interpreter of the current law, but also on the legislator. The author also analyzes the modern trends of law-making in the process of administration of justice, thereby outlining the interrelationships of judicial law-making and justice. Were revealed the basics of the problem of the application of legal doctrines as a source of persuasive character in the resolution of tax disputes in court and were formulated conclusions and proposals for the use of such legal instruments in order to improve modern law-making processes.